2023
DOI: 10.3389/fnut.2023.1105254
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and diabetes mellitus among people living with and without HIV: a cross-sectional study in Tanzania

Abstract: BackgroundDue to the complexity of human diets, it is difficult to relate single foods to health outcomes. We aimed to identify the dietary patterns and associated factors and to assess the association of dietary patterns with prediabetes/diabetes among adults living with and without HIV in Tanzania.MethodsDiet data were collected by a food frequency questionnaire (FFQ) and dietary patterns were derived by principal component analysis (PCA) and reduced rank regression (RRR). The associations between dietary pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In a cross-sectional study from Tanzania, it was concluded that a diet that is not rich in vegetables among older PLWH is positively correlated with the development of type 2 diabetes. 40 Among the older PLWH, older men consumed a carbohydrate-rich diet with lesser proportions of vegetables in comparison to older women 40 The recommendation to provide health education on a vegetable-rich diet with less carbohydrates is validated in a mixed-methods exploratory study conducted in the UK among older PLWH. This study found that adherence to a diet consisting of at least seven servings of fruit and vegetables daily, with restrictions in carbohydrate to 600 kcal with 50% being whole grains, sugar to 25 mg and restrictions of oil to less than 10% of all total energy intake resulted in lowering of type 2 diabetes indicators.…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study from Tanzania, it was concluded that a diet that is not rich in vegetables among older PLWH is positively correlated with the development of type 2 diabetes. 40 Among the older PLWH, older men consumed a carbohydrate-rich diet with lesser proportions of vegetables in comparison to older women 40 The recommendation to provide health education on a vegetable-rich diet with less carbohydrates is validated in a mixed-methods exploratory study conducted in the UK among older PLWH. This study found that adherence to a diet consisting of at least seven servings of fruit and vegetables daily, with restrictions in carbohydrate to 600 kcal with 50% being whole grains, sugar to 25 mg and restrictions of oil to less than 10% of all total energy intake resulted in lowering of type 2 diabetes indicators.…”
Section: Resultsmentioning
confidence: 99%